Innovating Islamic religious education methods through differentiated instruction: Enhancing learning motivation and understanding of religious concepts - Hardiansyah, Ilham Cahya; Afifah, Imroatul; Mardiana, Dina (TAWAZUN: Jurnal Pendidikan Islam, 2025)
Islamic Religious Education in elementary schools requires an adaptive instructional approach to address the diverse readiness levels and learning styles of students. This study aims to analyze the strategies employed by teachers in impelementing differentiated instruction and its impact on student’s learning motivation and religious character formation. A descriptive qualitative method was applied through observation, interviews and documentation involving sixth grade Islamic education classes. The findings reveal that teachers implemented differentiation in content, process, and product by adjusting to students’ Qur’an reading proficiency, learning style preferences, and personal interests. This strategy significantly enhanced students’ active participation, confidence in expressing opinions, and intrinsic motivation driven by spiritual awareness, as indicated by voluntary engagement in religious practices such as Dhuha prayer and independent Qur’an recitation. Moreover, religious character traits such as honesty, discipline, and responsibility were fostered through authentic and personalized learning experiences. The novelty of this study lies in its emphasis that differentiated instruction in Islamic Education functions not merely as an adaptive pedagogical technique but as an instrument of conscious and humanistic value internalization rather than compliance-based religiosity. These findings provide strategic implications for developing a more personal, inclusive, and spiritually grounded PAI learning model rooted in students’ individual fitrah. Abstrak Pendidikan Agama Islam di sekolah dasar membutuhkan pendekatan pembelajaran yang adaptif untuk mengatasi tingkat kesiapan dan gaya belajar siswa yang beragam. Penelitian ini bertujuan untuk menganalisis strategi yang digunakan oleh guru dalam mengimplementasikan pengajaran berdiferensiasi dan dampaknya terhadap motivasi belajar dan pembentukan karakter religius siswa. Metode kualitatif deskriptif diterapkan melalui observasi, wawancara dan dokumentasi yang melibatkan kelas pendidikan agama Islam kelas enam. Temuan menunjukkan bahwa guru menerapkan diferensiasi dalam konten, proses, dan produk dengan menyesuaikan pada kemampuan membaca Al-Qur'an siswa, preferensi gaya belajar, dan minat pribadi. Strategi ini secara signifikan meningkatkan partisipasi aktif siswa, kepercayaan diri dalam menyampaikan pendapat, dan motivasi intrinsik yang didorong oleh kesadaran spiritual, seperti yang ditunjukkan oleh keterlibatan sukarela dalam praktik keagamaan seperti salat dhuha dan pembacaan Alquran secara mandiri. Selain itu, karakter religius seperti kejujuran, kedisiplinan, dan tanggung jawab dipupuk melalui pengalaman belajar yang otentik dan personal. Kebaruan dari penelitian ini terletak pada penekanannya bahwa pengajaran berdiferensiasi dalam Pendidikan Agama Islam tidak hanya berfungsi sebagai teknik pedagogis yang adaptif, tetapi juga sebagai instrumen internalisasi nilai secara sadar dan humanis, bukan sebagai religiusitas berbasis kepatuhan. Temuan ini memberikan implikasi strategis untuk mengembangkan model pembelajaran PAI yang lebih personal, inklusif, dan berlandaskan spiritual yang berakar pada fitrah individu siswa.